Research progress on the cross-regulation between ferroptosis and immunogenic cell death in tumor micro-environment - Liu, Weitao; Jing, Yichen; Chen, Yang; Sun, Han; Xu, Wenbo; Liang, Ruihan; Liu, Wanglin; Zhang, Zengyu; Liu, Huiping (Frontiers in Oncology, 2025)
Ferroptosis and immunogenic cell death, as two unique forms of cell death, have attracted extensive attention in the biomedical field. Recent studies have shown the synergistic effect of ICD and ferroptosis in the tumor microenvironment, where tumor cells undergo immunogenic cell death and release immunogenic molecules, such as DAMPs, to recruit and activate immune cells and promote adaptive immune responses. At the same time, molecules such as lipid peroxides produced by ferroptosis may also enhance the anti-tumor activity of immune cells. In addition, the synergistic use of ferroptosis and ICD in combination with novel protocols such as biomaterials and nanotechnology has demonstrated promising anti-tumor effects. This article reviews the cross-regulatory mechanism of ferroptosis and ICD in the tumor microenvironment, and explores the related biological effects between immune cells and ferroptosis, and the potential application of the two in the treatment of cancer. At the same time, we put forward insights into the solution of the existing problems in the combination of ferroptosis and ICD, as well as new ideas and development directions for future cancer treatment.